The investigation of active sites on nickel oxide based catalysts towards the in-situ reactions of methanation and desulfurization - Wan Abu Bakar, Wan Azelee (Canadian Center of Science and Education, 2009)
Supported nickel oxide based catalysts of Fe/ Co/ Ni (10: 30: 60)-Al2O3 and Pr/ Co/ Ni (5: 35: 60)-Al2O3 that were prepared by wetness impregnation method showed potential catalysts for the in-situ reactions of H2S desulfurization and CO2 methanation from ambient temperature up to 300 oC. X-ray Photoelectron Spectroscopy revealed Ni2O3 and Fe3O4 as the surface active components on the Fe/ Co/ Ni (10: 30: 60)-Al2O3 catalyst, while Ni2O3 and Co3O4 on the Pr/ Co/ Ni (5: 35: 60)-Al2O3 catalyst. Energy Dispersive X-ray analysis indicated the presence of 2.7 % and 0.9 % of sulfur on the spent Fe/ Co/ Ni (10: 30: 60)-Al2O3 and Pr/ Co/ Ni (5: 35: 60)-Al2O3 catalysts, respectively. N2 adsorption-desorption analysis showed reduction of 5.5 % on the surface area of the spent Fe/ Co/ Ni (10: 30: 60)-Al2O3 catalyst. However, the surface area of the spent Pr/ Co/ Ni (5: 35: 60)-Al2O3 catalyst increased by 8.6 %.